SYSTEMS-2: A randomised phase II study of radiotherapy dose escalation for pain control in malignant pleural mesothelioma. (January 2018) - Ashton, M.; O'Rourke, N.; Macleod, N.; Laird, B.; Stobo, J.; Kelly, C.; Alexander, L.; Franks, K.; Moore, K.; Currie, S.; Valentine, R.; Chalmers, A.J.
Highlights: A randomised phase II trial of radiotherapy dose escalation for pain control in MPM. Comparison of 2 hypofractionated regimes (20 Gy/5# and 36 Gy/6#). Highly conformal radiotherapy techniques used to aid safe dose escalation. Primary outcome: pain control at week 5 at radiotherapy site. Recruitment target: 112 patients from 10 to 15 UK centres. Abstract: SYSTEMS-2 is a randomised study of radiotherapy dose escalation for pain control in 112 patients with malignant pleural mesothelioma (MPM). Standard palliative (20 Gy/5#) or dose escalated treatment (36 Gy/6#) will be delivered using advanced radiotherapy techniques and pain responses will be compared at week 5. Data will guide optimal palliative radiotherapy in MPM.